Carga inmediata sobre implantes : una posibilidad protésica (2000)
ABSTRACT: Dr.Branemark introduced the term osseointegration as a new concept in endosseous implant therapy. Long-term follow-up studies demonstrated a high success rate. Surgical and prosthetic protocol established certain conditions to get osseointegration, permiting a long healing time, 3-6 months, without functional load. This original protocol has been changing over time. This review shows how the immediate load can be a prosthetic possibility in the osseointegration technique whitout being a risk factor.